Brain-Based Learning - Aliustaoğlu, Feyza; Tuna, Abdulkadir (IGI Global, 2021)
Many models that take into account the learning styles have been developed with the formation of modern educational approaches. 4MAT model is a natural learning process moving sequentially through the learning cycle. According to the 4MAT model there are four learning styles and each student can learn more comfortable with their own learning styles. In consideration of neurological studies, also, the dominant hemisphere used by individuals in the information processing process is important in the 4MAT model. This chapter presents a lesson plan based on the 4MAT model as well as the results regarding the application of this lesson plan in a middle school located in the northern part of Turkey. The lesson plan was prepared by examining the books titled “4MAT 4 algebra: The system of mathematics” and “4 MAT 4 geometry teacher book” and receiving expert opinions.
Keywords: 4. Education; 10. No inequality